A correlation study of mismatch repair immunohistochemical protein expression of pancreatic solid tumors in cytology cell blocks and matching surgical specimens. Issue 6 (21st February 2021) - Teodosescu, Andrei; Chan, Ina; Elder, Julie; Wu, Maoxin
Abstract: Introduction: Only 15%‐20% of newly diagnosed pancreatic ductal adenocarcinoma (PDAC) cases are surgically operable. Cytology samples may be the only source for guiding clinical management. Current research indicates that mismatch repair (MMR) status could be valuable for implementing novel treatment modalities. In this study, immunohistochemical (IHC) MMR protein expression on cytology cell blocks was compared with that of the correlating surgical resection specimens. Materials and Methods: A retrospective review of 120 pancreatic solid tumor needle biopsies from 2016 to 2019 was performed, and 15 experimental cases were selected comprising of cellular (>100 tumor cells and >100 benign positive control cells that include benign ductal cells and/or lymphocytes) alcohol‐prefixed formalin‐fixed cytology cell blocks (CB), and corresponding subsequent surgical resections (Surg). The cases include 13 PDACs (87%), 1 (6.5%) low grade neuroendocrine tumor (PNET), and 1 (6.5%) acinar cell carcinoma (ACC). A routine four‐panel (MLH1, MSH2, MSH6, and PMS2) MMR IHC testing was performed. The percentage of protein expression was evaluated and compared between individual CB‐Surg pairs. Results: About 8 of the 15 (53.3%) cytology cases showed matching protein expressivity with the surgical specimens for all four MMR markers (Table 1 ). The remaining 7 pairs (46.7%) appeared to have a partial concordance, including 6 values for which a surgical marker showed less expression, and 13 values for which a cytological marker showed less expression. Conclusion: Cytology CB MMR protein panel testing could be a useful consideration for inoperable patients who would benefit from medical therapy such as immune checkpoint inhibition. However, the cellularity and overall quality of the CB is expected to be paramount in obtaining satisfactory IHC MMR results. The MMR results could be more confidently trusted when the staining is intact, but when not retained, they should be interpreted with caution in a low cellularity sample to avoid mistakenly identifying MMR‐deficient tumors.